New taxa of Athyreacaridae (Acari: Heterostigmata) from Neotropical and Afrotropical realms - Khaustov, Alexander A.; Frolov, Andrey V. (Zootaxa, 2022)
A new genus and three new species of Athyreacaridae (Acari: Heterostigmata) are described associated with beetles of subfamily Bolboceratinae (Coleoptera: Geotrupidae) in Neotropical and Afrotropical realms: Neoathyreacarus pygmephoroides gen., sp. nov. collected on Bolborhinum tubericeps in Chile; Athyreacarus staturosus sp. nov. collected on Zefevazia cantisani  in Argentina; and Athyreacarus camerikae sp. nov. collected on Namibiobolbus helgae in South Africa. An updated key to genera and species of Athyreacaridae is provided. Athyreacarus staturosus sp. nov. is the largest ever described non-physogastric female among Heterostigmata.